LA RAPPRESENTAZIONE CATALETTICA NELLA STOA POST-CRISIPPEA - Francesca Alesse (Lexicon Philosophicum)
The article aims to evaluate some appreciable contributions by post-Chrysippean Stoics to the theory of cognitive (kataleptic) impression and its role as a criterion of truth. The inquiry focuses on two testimonies: Sextus Empiricus, M, VII, 253-257, where we find a significant variation – introduced by some ‘recent Stoics’ – of the ancient Stoic theory of the clauses that an impression is supposed to satisfy in order to be considered not only kataleptic, i.e. worthy of assent, but also a criterion of truth; and PBerol. inv. 16545 containing the version of the theory of clauses of the cognitive impression developed by Antipater of Tarsus.